2009
DOI: 10.1007/s10571-009-9401-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to High Levels of Zinc or Copper has Little Effect on Brain Metal Homeostasis or Aβ Accumulation in Transgenic APP-C100 Mice

Abstract: Aberrant metal homeostasis may enhance the formation of reactive oxygen species and Abeta oligomerization and may therefore be a contributing factor in Alzheimer's disease. This study investigated the effect of chronic high intake of dietary Zn or Cu on brain metal levels and the accumulation and solubility of Abeta in vivo, using a transgenic mouse model that over expresses the C-terminal containing Abeta fragment of human amyloid precursor protein but does not develop amyloid deposits. Exposure to chronic hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Mice fed high dietary zinc showed significantly increased zinc level in serum and hemocytes, but the total brain zinc level was not changed. This result is consistent with previous research in which BL6/DBA mice were fed high zinc diets (300–1000 ppm) for 7–17 months, the brain zinc only showed a trend but no significant elevation [38]. Another study performed by Wang et al showed a significant increase of brain zinc in transgenic APP/PS1 mice fed a high zinc diet [31], but the dosage of supplemented zinc was extremely high (ZnSO4·7H2O 20 mg/ml in drink water, which equals to about 4530 ppm Zn), which may not occur in human.…”
Section: Discussionsupporting
confidence: 93%
“…Mice fed high dietary zinc showed significantly increased zinc level in serum and hemocytes, but the total brain zinc level was not changed. This result is consistent with previous research in which BL6/DBA mice were fed high zinc diets (300–1000 ppm) for 7–17 months, the brain zinc only showed a trend but no significant elevation [38]. Another study performed by Wang et al showed a significant increase of brain zinc in transgenic APP/PS1 mice fed a high zinc diet [31], but the dosage of supplemented zinc was extremely high (ZnSO4·7H2O 20 mg/ml in drink water, which equals to about 4530 ppm Zn), which may not occur in human.…”
Section: Discussionsupporting
confidence: 93%
“…28, 29 In the context of AD, however, studies on Zn 2+ deficiency or supplementation in AD models have provided conflicting results. 14, 15, 30 Here, we show that dietary Zn 2+ supplementation prevents hippocampal-dependent cognitive deficits, reduces both intraneuronal A β and tau pathology, prevents mitochondrial deficits and restores BDNF levels in a mouse model of AD.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, a recent study involving APP/PS1 mice fed a zinc-deficient diet has shown that such a diet increases the plaque volume but does not alter the total plaque number in the brain [27]. Chronic high zinc- or copper-treated mice overexpress APP-C100, which contains Aβ but not the N-terminal zinc and copper binding domain of APP, resulting in reduced soluble Aβ levels but with no changes in the total Aβ levels in the brain [54]. It has also been reported that exposure to copper and, presumably, a mixture of other metals in drinking water results in enhanced Aβ deposition in the brains of rabbits fed a high cholesterol diet [55].…”
Section: Discussionmentioning
confidence: 99%